Feasibility of Telerehabilitation Implementation as a Novel Experience in Rehabilitation Academic Centers and Affiliated Clinics in Tehran: Assessment of Rehabilitation Professionals’ Attitudes - Sara Movahedazarhouligh; Roshanak Vameghi; Nikta Hatamizadeh; Enayatollah Bakhshi; Seyed Muhammad Moosavy Khatat (International Journal of Telemedicine and Applications)
Introduction. This study aimed to assess rehabilitation professionals’ attitude toward implementation and application of telerehabilitation technology as a novel study in rehabilitation academic centers and affiliated clinics in Tehran. Methods. It was a descriptive cross-sectional study. To collect data, a researcher-designed questionnaire was developed. 141 rehabilitation experts participated in the study. Results. A majority of faculty members (78%) and clinicians (89.7%) either were in “definite agreement” or “somewhat agreed” with implementation and application of this technology, which demonstrates an overall positive attitude. Discussion. Based on the positive attitudes of the majority of participants toward implementation and application of this technology and their preferences in offering different telerehabilitation services, it seems that there is an appropriate and desirable acceptance and administrative culture to implement this technology among rehabilitation experts in Tehran. It is thus expected that implementation and application of this technology will be a promising experience in rehabilitation academic centers and affiliate clinics in Tehran.